The synthesis and host-guest activity of novel cyanoborate salts - Haueisen, Renate H (Department of Chemistry, 2016)
Molecular recognition is a dynamic process based on distinct chemical interactions and not on passive fitting of a lock and key. Complex formation between host and guest molecules is often accompanied by conformational reorganisation, which makes it possible to engineer and fine-tune synthetic receptor analogues for optimal function and selectivity. This thesis primarily describes a supramolecular study of a novel family of airstable cyanoborate host compounds. The discovery of this clathrand family came about as a result of a study relating to the synthesis of an electrolyte for the Zebra car battery and the thesis begins with this aspect (Chapter 1). Although cyanoborates are well documented as synthetic intermediates in 1,2 migration reactions they have not been studied independently to any degree and this thesis constitutes the first significant study of this class of compound.